Method for detecting nicotine based on molecularly imprinted polymer sensor and application
Through a molecularly imprinted polymer sensor method, graphene oxide and platinum nanoparticles are used to modify the glass carbon electrode, combined with differential pulse voltammetry, the complexity and cost of nicotine detection in tobacco products is solved, achieving rapid and accurate The nicotine content analysis is suitable for on-site and large-scale testing.
Patent Information
- Application Number
- CN202411763886.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-14
AI Technical Summary
The nicotine detection methods in existing tobacco products are complex, expensive, and are not suitable for rapid on-site analysis or high-throughput screening, making it difficult to meet the accurate and rapid detection of nicotine content.
Using a method based on molecularly imprinted polymer sensor, glass carbon electrodes are modified by graphene oxide and platinum nanoparticles, combined with differential pulse voltammetry, to achieve rapid and accurate detection of nicotine in tobacco products.
It realizes rapid analysis of nicotine content in tobacco products and large-scale sample detection, which is low cost, simple operation, accurate detection results, and suitable for on-site applications.
Smart Images

Figure CN119310158A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of tobacco product analysis and detection, and in particular relates to a method and application of nicotine detection based on a molecular imprinting polymer sensor. Background Art
[0002] Nicotine is a naturally occurring alkaloid found in tobacco plants that is highly addictive and is the main ingredient in tobacco products that cause dependence. The use of cigarettes and other forms of tobacco products is a major health problem worldwide, killing millions of people each year and leading to a variety of chronic diseases, including lung cancer, cardiovascular disease, and respiratory diseases. As science and technology advance, researchers are increasingly aware of the adverse health effects of nicotine and tobacco product use, which means that more accurate and reliable testing methods are needed to quantify the nicotine content in tobacco products. Monitoring nicotine levels is essential for assessing the addictiveness and health risks associated with tobacco products, as well as for regulatory purposes and research on tobacco-related health issues.
[0003] Traditional analytical testing methods for detecting nicotine content in tobacco samples include gas chromatography (GC), high performance liquid chromatography (HPLC) and mass spectrometry (MS). Although these traditional methods have high sensitivity and accuracy, they usually require complex sample preparation, expensive instruments and skilled operators, which makes the analysis process time-consuming and expensive. In addition, these techniques may not be suitable for rapid on-site analysis or high-throughput screening. Summary of the invention
[0004] The purpose of the present invention is to provide a method and application of detecting nicotine based on a molecular imprinting polymer sensor, so as to achieve rapid and accurate detection of nicotine content in tobacco products, so as to solve the problems existing in the background technology.
[0005] To achieve the above objectives, this application is implemented through the following technical solutions:
[0006] A method for detecting nicotine based on a molecular imprinting polymer sensor comprises the following steps:
[0007] S1. Synthesis of graphene oxide:
[0008] Graphite powder and concentrated sulfuric acid are mixed in an ice bath, potassium permanganate and sodium nitrate are slowly added to the mixed solution under stirring, the mixture is heated to 35-40°C and stirred for 2 hours, deionized water is then added to the mixture, the temperature is raised to 90-100°C, and after maintaining for 15-25 minutes, deionized water and 30% hydrogen peroxide are added to the heated mixture to obtain a suspension of graphene oxide, the suspension is centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide;
[0009] S2. Preparation of platinum nanoparticles:
[0010] The hexahydrate chloroplatinic acid solution and the sodium dodecyl sulfate solution were mixed under vigorous stirring, and then ascorbic acid was added to the mixed solution. After stirring for 2 h, the mixture was centrifuged and washed with deionized water and dispersed with ethanol to obtain platinum nanoparticles.
[0011] S3. Preparation of PtNPs / graphene oxide nanocomposites:
[0012] The graphene oxide obtained in step S1 is dispersed in deionized water, and ultrasonicated for 30 minutes to obtain a graphene oxide dispersion, and the PtNPs suspension is added to the graphene oxide dispersion, stirred for 10-14 hours, and then centrifuged, washed with deionized water, and dried at 60° C. to obtain a PtNPs / graphene oxide nanocomposite material;
[0013] S4. Preparation of PtNPs / graphene oxide modified glassy carbon electrode:
[0014] The glassy carbon electrode was polished with alumina slurry, ultrasonicated in ethanol and deionized water, and dried under nitrogen flow. The PtNPs / graphene oxide nanocomposite was ultrasonically dispersed in deionized water for 30 min, and then the dispersed suspension was dropped onto the surface of the glassy carbon electrode and dried at room temperature to obtain a PtNPs / graphene oxide modified glassy carbon electrode.
[0015] S5. Preparation of nicotine molecularly imprinted polymer sensing electrode:
[0016] The acetonitrile solution of pyridine, nicotine and potassium perchlorate is mixed to obtain an electropolymerization solution, and the electropolymerization solution is electropolymerized in the potential range of 0.1-1.6V by cyclic voltammetry, with a scanning rate of 50 mV / s and 10-15 cycles. After the electropolymerization reaction, the electrode is rinsed with acetonitrile, and then the electrode is immersed in a solution of NaCl and HCl, stirred for 30 minutes, and then rinsed with deionized water, and dried under a nitrogen flow, thereby obtaining a nicotine molecular imprinted polymer sensing electrode;
[0017] S6. Preparation of tobacco product samples:
[0018] Take tobacco samples, extract them with methanol or ethanol ultrasonically for 30 minutes, filter the extract and dilute it with phosphate buffered saline;
[0019] S7. Detection of nicotine in tobacco product samples:
[0020] The nicotine molecular imprinted polymer sensing electrode was immersed in the tobacco extract diluted in step S6 for 10 minutes, after which the electrode was rinsed with phosphate buffered saline and transferred to fresh phosphate buffered saline for differential pulse voltammetry measurement. The nicotine concentration in the tobacco sample was determined using a calibration curve of a standard nicotine solution.
[0021] Furthermore, in step S1, the mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate is 1:80-110:2-5:10-20; the volume ratio of the mixture and deionized water is 1:1.5-3; and after heating, the volume ratio of the mixture, deionized water and hydrogen peroxide is 1:1-2:0.05-0.2.
[0022] Furthermore, in step S2, the volume ratio of the hexahydrate chloroplatinic acid solution to the sodium dodecyl sulfate solution is 1:1-2; and the mass ratio of the mixed solution to ascorbic acid is 200-300:1.
[0023] Furthermore, in step S3, the mass ratio of graphene oxide to deionized water is 1:2-4; the volume ratio of graphene oxide dispersion to PtNPs suspension is 1:0.1-0.3.
[0024] Further, in step S4, the glassy carbon electrode is polished with 0.3 μm and 0.05 μm alumina slurries, respectively, and the mass ratio of the PtNPs / graphene oxide nanocomposite material to deionized water is 1:800-1200.
[0025] Furthermore, in step S5, 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile are mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile is 1:1-3:2-5 to obtain an electropolymerization solution.
[0026] Further, in step S5, the electrode is immersed in a solution of 0.5 M NaCl and 0.1 M HCl, and the volume ratio of NaCl to HCl is 1:1-2.
[0027] Furthermore, in step S6, the mass ratio of the tobacco sample to the extractant is 1:5-10, the extract is filtered through a 0.22 μm nylon syringe, and then diluted with a 0.1 M phosphate buffered saline solution with a pH of 7.4, and the volume ratio of the extract to the phosphate buffered saline solution is 1:5-10.
[0028] Further, in step S7, differential pulse voltammetry measurement is performed in the potential range of 0.2-0.8 V, with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
[0029] An application, using any of the above methods for detecting nicotine based on a molecular imprinting polymer sensor in detecting nicotine.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The molecular imprinting polymer sensor electrode analysis technology can be used to analyze and detect the nicotine content in tobacco products on site, thus achieving rapid analysis of samples.
[0032] 2. Use electrochemical workstation to realize centralized testing of large quantities of samples, which is low-cost, convenient and efficient.
[0033] 3. This technology has accurate detection content, simple detection process, easy operation and easy promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope image of graphene oxide of the present invention.
[0035] Figure 2 This is a scanning electron microscope image of the PtNPs / graphene oxide nanocomposite material of the present invention.
[0036] Figure 3 This is an energy spectrum analysis diagram of the PtNPs / graphene oxide nanocomposite material of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings. The following embodiments are merely exemplary and can only be used to explain and illustrate the technical solution of the present invention, but cannot be construed as limiting the technical solution of the present invention.
[0038] The present invention provides a method for detecting nicotine content in tobacco products based on a molecular imprinting polymer sensor, comprising the following steps:
[0039] S1. Synthesis of graphene oxide (GO):
[0040] Graphite powder and concentrated sulfuric acid are mixed in an ice bath, and potassium permanganate and sodium nitrate are slowly added to the mixed solution under stirring. The mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate is 1:80-110:2-5:10-20. The mixture is then heated to 35-40°C and stirred for 2 h. Subsequently, deionized water is added to the mixture, and the volume ratio of the mixture to deionized water is 1:1.5-3. The temperature is raised to 90-100°C and maintained for 15-25 min. Deionized water and 30% hydrogen peroxide are added to the heated mixture. The volume ratio of the mixture, deionized water and hydrogen peroxide after heating is 1:1-2:0.05-0.2 to obtain a suspension of graphene oxide. The suspension is centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide (GO). Scanning electron microscopy of GO shows Figure 1 .
[0041] S2. Preparation of platinum nanoparticles (PtNPs):
[0042] 1 mM hexahydrate chloroplatinic acid solution and 0.1 M sodium dodecyl sulfate solution were mixed under vigorous stirring, and the volume ratio of hexahydrate chloroplatinic acid solution to sodium dodecyl sulfate solution was 1:1-2. Then ascorbic acid was added to the mixed solution, and the mass ratio of the mixed solution to ascorbic acid was 200-300:1. After stirring for 2 hours, the mixture was centrifuged, washed with deionized water, and dispersed with ethanol to obtain platinum nanoparticles.
[0043] S3. Preparation of PtNPs / GO nanocomposites:
[0044] GO was dispersed in deionized water, the mass ratio of GO to deionized water was 1:2-4, and ultrasonic was applied for 30 min to obtain GO dispersion. PtNPs suspension was added to GO dispersion, the volume ratio of GO dispersion to PtNPs suspension was 1:0.1-0.3, stirred for 10-14 h, centrifuged, washed with deionized water, and dried at 60°C to obtain PtNPs / GO nanocomposite. Scanning electron microscopy of PtNPs / GO nanocomposite was shown. Figure 2 , energy spectrum analysis see Figure 3 .
[0045] S4. Preparation of PtNPs / GO modified glassy carbon electrode (PtNPs / GO / GCE):
[0046] Glassy carbon electrodes (GCE) were polished with 0.3 μm and 0.05 μm alumina slurries, respectively, ultrasonicated in ethanol and deionized water, respectively, and dried under nitrogen flow. PtNPs / GO nanocomposites were ultrasonically dispersed in deionized water for 30 min, with a mass ratio of PtNPs / GO nanocomposites to deionized water of 1:800-1200, and then 3-8 μL of the dispersed suspension was dropped onto the GCE surface and dried at room temperature to obtain PtNPs / GO modified GCE.
[0047] S5. Preparation of nicotine molecularly imprinted polymer (MIP) sensing electrode (MIP / PtNPs / GO / GCE):
[0048] 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile were mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile was 1:1-3:2-5 to obtain an electropolymerization solution. The electropolymerization solution was electropolymerized by cyclic voltammetry (CV) in the potential range of 0.1-1.6 V (vs. Ag / AgCl), with a scan rate of 50 mV / s and 10-15 cycles. After the electropolymerization reaction, the electrode was rinsed with acetonitrile. Subsequently, the electrode was immersed in a solution of 0.5 M NaCl and 0.1 M HCl, with a volume ratio of NaCl to HCl of 1:1-2. After stirring for 30 min, the electrode was rinsed with deionized water and dried under a nitrogen flow to obtain a nicotine molecularly imprinted polymer sensing electrode.
[0049] S6. Preparation of tobacco product samples:
[0050] Tobacco samples, including but not limited to traditional cigarettes and chewing tobacco, were purchased from the local market and ultrasonically extracted with methanol or ethanol for 30 minutes. The mass ratio of tobacco sample to extractant was 1:5-10. The extract was filtered through a 0.22 μm nylon syringe and diluted with 0.1 M phosphate buffered saline (pH 7.4). The volume ratio of the extract to phosphate buffered saline was 1:5-10.
[0051] S7. Nicotine detection in tobacco product samples:
[0052] The MIP / PtNPs / GO / GCE electrode was immersed in the diluted tobacco extract for 10 minutes, after which the electrode was rinsed with 0.1 M phosphate buffered saline and transferred to fresh phosphate buffered saline for differential pulse voltammetry (DPV) measurement. The nicotine concentration in the tobacco sample was determined using the calibration curve of the standard nicotine solution. The DPV measurement was performed in the potential range of 0.2-0.8 V (vs. Ag / AgCl), with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
[0053] Example 1
[0054] Application of molecular imprinting polymer sensor to detect nicotine content in HOMER (natural smoke original flavor).
[0055] Preparation of molecularly imprinted polymer sensors:
[0056] S1. Synthesis of graphene oxide (GO):
[0057] Graphite powder and concentrated sulfuric acid were mixed in an ice bath, and potassium permanganate and sodium nitrate were slowly added to the mixed solution under stirring. The mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate was 1:80:2:1:15. The mixture was then heated to 35°C and stirred for 2 h. Subsequently, deionized water was added to the mixture, and the volume ratio of the mixture to deionized water was 1:1.5. The mixture was heated to 90°C and kept for 15 min. Deionized water and 30% hydrogen peroxide were added to the heated mixture, and the volume ratio of the mixture, deionized water and hydrogen peroxide was 1:1:0.05 after heating, to obtain a suspension of graphene oxide. The suspension was centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide (GO).
[0058] S2. Preparation of platinum nanoparticles (PtNPs):
[0059] 1 mM hexahydrate chloroplatinic acid solution and 0.1 M sodium dodecyl sulfate solution were mixed under vigorous stirring, and the volume ratio of hexahydrate chloroplatinic acid solution to sodium dodecyl sulfate solution was 1: 1. Then ascorbic acid was added to the mixed solution, and the mass ratio of the mixed solution to ascorbic acid was 200: 1. After stirring for 2 h, the mixture was centrifuged, washed with deionized water, and dispersed with ethanol to obtain platinum nanoparticles.
[0060] S3. Preparation of PtNPs / GO nanocomposites:
[0061] GO was dispersed in deionized water, the mass ratio of GO to deionized water was 1:2, and ultrasonic treatment was performed for 30 min to obtain a GO dispersion. PtNPs suspension was added to the GO dispersion, the volume ratio of GO dispersion to PtNPs suspension was 1:0.1, stirred for 10 h, centrifuged, washed with deionized water, and dried at 60°C to obtain a PtNPs / GO nanocomposite.
[0062] S4. Preparation of PtNPs / GO modified glassy carbon electrode (PtNPs / GO / GCE):
[0063] Glassy carbon electrodes (GCE) were polished with 0.3 μm and 0.05 μm alumina slurries, respectively, ultrasonicated in ethanol and deionized water, respectively, and dried under nitrogen flow. PtNPs / GO nanocomposites were ultrasonically dispersed in deionized water for 30 min, with a mass ratio of PtNPs / GO nanocomposites to deionized water of 1:800, and then 3 μL of the dispersed suspension was dropped onto the GCE surface and dried at room temperature to obtain PtNPs / GO modified GCE.
[0064] S5. Preparation of nicotine molecularly imprinted polymer (MIP) sensing electrode (MIP / PtNPs / GO / GCE):
[0065] 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile were mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile was 1:1:2 to obtain an electropolymerization solution. The electropolymerization solution was electropolymerized by cyclic voltammetry (CV) in the potential range of 0.1-1.6V (vs. Ag / AgCl), with a scan rate of 50 mV / s and 10 cycles. After the electropolymerization reaction, the electrode was rinsed with acetonitrile. Subsequently, the electrode was immersed in a solution of 0.5 M NaCl and 0.1 M HCl, with a volume ratio of NaCl and HCl of 1:1. After stirring for 30 min, the electrode was rinsed with deionized water and dried under a nitrogen flow to obtain a nicotine molecularly imprinted polymer sensing electrode.
[0066] S6. HOMER (natural smoke original flavor) tobacco was ultrasonically extracted with methanol for 30 minutes. The mass ratio of HOMER (natural smoke original flavor) tobacco to methanol was 1:5. The extract was filtered through a 0.22 μm nylon syringe and diluted with 0.1 M phosphate buffered saline (pH 7.4). The volume ratio of the extract to the phosphate buffered saline was 1:5.
[0067] S7. Soak the MIP / PtNPs / GO / GCE sensing electrode in the diluted tobacco extract for 10 minutes, then rinse the electrode with 0.1M phosphate buffered saline and transfer it to fresh phosphate buffered saline for differential pulse voltammetry (DPV) measurement. The nicotine concentration in the tobacco sample was determined using the calibration curve of the standard nicotine solution. The DPV measurement was performed in the potential range of 0.2-0.8 V (vs. Ag / AgCl), with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
[0068] The nicotine content in HOMER (natural smoke flavor) was 12.65±0.48 mg / g after three measurements by the MIP / PtNPs / GO / GCE sensor electrode, and the nicotine content of this brand of cigarettes was 12.92±0.39 after three tests by gas chromatography-mass spectrometry. The measurement deviation of the MIP / PtNPs / GO / GCE sensor electrode was 2.1%, indicating that the accuracy in this aspect was relatively high.
[0069] Example 2
[0070] Application of molecularly imprinted polymer sensor for detection of nicotine content in golden leaf (mango).
[0071] Preparation of molecularly imprinted polymer sensors:
[0072] S1. Synthesis of graphene oxide (GO):
[0073] Graphite powder and concentrated sulfuric acid were mixed in an ice bath, and potassium permanganate and sodium nitrate were slowly added to the mixed solution under stirring. The mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate was 1:97:3.5:12. The mixture was then heated to 38°C and stirred for 2 h. Subsequently, deionized water was added to the mixture, and the volume ratio of the mixture to deionized water was 1:2. The mixture was heated to 97°C and kept for 20 min. Deionized water and 30% hydrogen peroxide were added to the heated mixture. The volume ratio of the mixture, deionized water and hydrogen peroxide after heating was 1:1.6:0.1 to obtain a suspension of graphene oxide. The suspension was centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide (GO).
[0074] S2. Preparation of platinum nanoparticles (PtNPs):
[0075] 1 mM hexahydrate chloroplatinic acid solution and 0.1 M sodium dodecyl sulfate solution were mixed under vigorous stirring, and the volume ratio of hexahydrate chloroplatinic acid solution to sodium dodecyl sulfate solution was 1:1.5. Then ascorbic acid was added to the mixed solution, and the mass ratio of the mixed solution to ascorbic acid was 230-300:1. After stirring for 2 hours, the mixture was centrifuged, washed with deionized water, and dispersed with ethanol to obtain platinum nanoparticles.
[0076] S3. Preparation of PtNPs / GO nanocomposites:
[0077] GO was dispersed in deionized water, the mass ratio of GO to deionized water was 1:3, and ultrasonic treatment was performed for 30 min to obtain a GO dispersion. PtNPs suspension was added to the GO dispersion, the volume ratio of GO dispersion to PtNPs suspension was 1:0.2, stirred for 12 h, centrifuged, washed with deionized water, and dried at 60°C to obtain a PtNPs / GO nanocomposite.
[0078] S4. Preparation of PtNPs / GO modified glassy carbon electrode (PtNPs / GO / GCE):
[0079] Glassy carbon electrodes (GCE) were polished with 0.3 μm and 0.05 μm alumina slurries, respectively, ultrasonicated in ethanol and deionized water, respectively, and dried under nitrogen flow. PtNPs / GO nanocomposites were ultrasonically dispersed in deionized water for 30 min, with a mass ratio of PtNPs / GO nanocomposites to deionized water of 1:1000, and then 5 μL of the dispersed suspension was dropped onto the GCE surface and dried at room temperature to obtain PtNPs / GO modified GCE.
[0080] S5. Preparation of nicotine molecularly imprinted polymer (MIP) sensing electrode (MIP / PtNPs / GO / GCE):
[0081] 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile were mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile was 1:2:3 to obtain an electropolymerization solution. The electropolymerization solution was electropolymerized by cyclic voltammetry (CV) in the potential range of 0.1-1.6V (vs. Ag / AgCl), with a scan rate of 50 mV / s and 10-15 cycles. After the electropolymerization reaction, the electrode was rinsed with acetonitrile. Subsequently, the electrode was immersed in a solution of 0.5 M NaCl and 0.1 M HCl, with a volume ratio of NaCl to HCl of 1:1.4. After stirring for 30 min, the electrode was rinsed with deionized water and dried under a nitrogen flow to obtain a nicotine molecularly imprinted polymer sensing electrode.
[0082] S6. Ultrasonic extraction of golden leaf (mango) tobacco was performed with methanol for 30 minutes. The mass ratio of golden leaf (mango) tobacco to methanol was 1:10. The extract was filtered through a 0.22 μm nylon syringe and diluted with 0.1 M phosphate buffered saline (pH 7.4). The volume ratio of the extract to phosphate buffered saline was 1:8.
[0083] S7. Soak the MIP / PtNPs / GO / GCE electrode in the diluted tobacco extract for 10 minutes, then rinse the electrode with 0.1 M phosphate buffered saline and transfer it to fresh phosphate buffered saline for differential pulse voltammetry (DPV) measurement. The nicotine concentration in the tobacco sample was determined using the calibration curve of the standard nicotine solution. The DPV measurement was performed in the potential range of 0.2-0.8 V (vs. Ag / AgCl), with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
[0084] The nicotine content in golden leaf (mango) was 11.24±0.43 mg / g after three measurements by MIP / PtNPs / GO / GCE sensor electrode, and the nicotine content of this brand of cigarette was 11.56±0.36 after three tests by gas chromatography-mass spectrometry. The measurement deviation of MIP / PtNPs / GO / GCE sensor electrode was 2.7%, indicating that the accuracy in this aspect was relatively high.
[0085] Example 3
[0086] Application of molecular imprinted polymer sensor to detect nicotine content in SUPEROUSE nicotine pouches.
[0087] Preparation of molecularly imprinted polymer sensors:
[0088] S1. Synthesis of graphene oxide (GO):
[0089] Graphite powder and concentrated sulfuric acid were mixed in an ice bath, and potassium permanganate and sodium nitrate were slowly added to the mixed solution under stirring. The mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate was 1:110:5:18. The mixture was then heated to 40°C and stirred for 2 h. Subsequently, deionized water was added to the mixture, and the volume ratio of the mixture to deionized water was 1:3. The mixture was heated to 100°C and kept for 25 min. Deionized water and 30% hydrogen peroxide were added to the heated mixture, and the volume ratio of the mixture, deionized water and hydrogen peroxide was 1:2:0.2 after heating, to obtain a suspension of graphene oxide. The suspension was centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide (GO).
[0090] S2. Preparation of platinum nanoparticles (PtNPs): 1 mM hexahydrate chloroplatinic acid solution and 0.1 M sodium dodecyl sulfate solution were mixed under vigorous stirring, and the volume ratio of hexahydrate chloroplatinic acid solution to sodium dodecyl sulfate solution was 1:2. Then ascorbic acid was added to the mixed solution, and the mass ratio of the mixed solution to ascorbic acid was 270-300:1. After stirring for 2 h, the mixture was centrifuged, washed with deionized water, and dispersed with ethanol to obtain platinum nanoparticles.
[0091] S3. Preparation of PtNPs / GO nanocomposites:
[0092] GO was dispersed in deionized water, the mass ratio of GO to deionized water was 1:4, and ultrasonic treatment was performed for 30 min to obtain a GO dispersion. PtNPs suspension was added to the GO dispersion, the volume ratio of GO dispersion to PtNPs suspension was 1:0.3, stirred for 14 h, centrifuged, washed with deionized water, and dried at 60°C to obtain a PtNPs / GO nanocomposite.
[0093] S4. Preparation of PtNPs / GO modified glassy carbon electrode (PtNPs / GO / GCE):
[0094] Glassy carbon electrodes (GCE) were polished with 0.3 μm and 0.05 μm alumina slurries, respectively, ultrasonicated in ethanol and deionized water, respectively, and dried under nitrogen flow. PtNPs / GO nanocomposites were ultrasonically dispersed in deionized water for 30 min, with a mass ratio of PtNPs / GO nanocomposites to deionized water of 1:1200, and then 8 μL of the dispersed suspension was dropped onto the GCE surface and dried at room temperature to obtain PtNPs / GO modified GCE.
[0095] S5. Preparation of nicotine molecularly imprinted polymer (MIP) sensing electrode (MIP / PtNPs / GO / GCE): 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile were mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile was 1:3:5 to obtain an electropolymerization solution. The electropolymerization solution was electropolymerized by cyclic voltammetry (CV) in the potential range of 0.1-1.6 V (vs. Ag / AgCl), with a scan rate of 50 mV / s and 15 cycles. After the electropolymerization reaction, the electrode was rinsed with acetonitrile. Subsequently, the electrode was immersed in a solution of 0.5 M NaCl and 0.1 M HCl, with a volume ratio of NaCl to HCl of 1:2. After stirring for 30 min, the electrode was rinsed with deionized water and dried under a nitrogen flow to obtain a nicotine molecularly imprinted polymer sensing electrode.
[0096] S6. Ultrasonic extraction of SUPEROUSE nicotine bag with ethanol for 30 minutes, the mass ratio of SUPEROUSE nicotine bag to ethanol is 1:10, the extract is filtered through a 0.22 μm nylon syringe, and diluted with 0.1 M phosphate buffered saline (pH 7.4), the volume ratio of the extract to phosphate buffered saline is 1:10.
[0097] S7. Soak the MIP / PtNPs / GO / GCE electrode in the diluted tobacco extract for 10 minutes, then rinse the electrode with 0.1 M phosphate buffered saline and transfer it to fresh phosphate buffered saline for differential pulse voltammetry (DPV) measurement. The nicotine concentration in the tobacco sample was determined using the calibration curve of the standard nicotine solution. The DPV measurement was performed in the potential range of 0.2-0.8 V (vs. Ag / AgCl), with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
[0098] The nicotine content in the SUPEROUSE nicotine bag was 7.98±0.42 mg / g after three measurements by the MIP / PtNPs / GO / GCE sensor electrode, and the nicotine content of this brand of cigarettes was 8.18±0.34 after three tests by gas chromatography-mass spectrometry. The measurement deviation of the MIP / PtNPs / GO / GCE sensor electrode was 2.5%, indicating that the accuracy in this aspect was relatively high.
[0099] The above description is only a part of the specific embodiments of the present application and is not intended to limit the present application. For relevant technical personnel in the field, the present application has various changes and variations. Any modification and replacement made within the relevant principles and implementation methods of the present application should be included in the scope of protection of the present application.
Claims
1. A method for detecting nicotine based on a molecular imprinting polymer sensor, characterized in that: The following steps are involved: S1. Synthesis of graphene oxide: Graphite powder and concentrated sulfuric acid are mixed in an ice bath, potassium permanganate and sodium nitrate are slowly added to the mixed solution under stirring, the mixture is heated to 35-40°C and stirred for 2 hours, deionized water is then added to the mixture, the temperature is raised to 90-100°C, and after maintaining for 15-25 minutes, deionized water and 30% hydrogen peroxide are added to the heated mixture to obtain a suspension of graphene oxide, the suspension is centrifuged, washed with 10% hydrochloric acid and deionized water, and dried at 60°C to obtain graphene oxide; S2. Preparation of platinum nanoparticles: The hexahydrate chloroplatinic acid solution and the sodium dodecyl sulfate solution were mixed under vigorous stirring, and then ascorbic acid was added to the mixed solution. After stirring for 2 h, the mixture was centrifuged and washed with deionized water and dispersed with ethanol to obtain platinum nanoparticles. S3. Preparation of PtNPs / graphene oxide nanocomposites: The graphene oxide obtained in step S1 is dispersed in deionized water, and ultrasonicated for 30 minutes to obtain a graphene oxide dispersion, and the PtNPs suspension is added to the graphene oxide dispersion, stirred for 10-14 hours, and then centrifuged, washed with deionized water, and dried at 60° C. to obtain a PtNPs / graphene oxide nanocomposite material; S4. Preparation of PtNPs / graphene oxide modified glassy carbon electrode: The glassy carbon electrode was polished with alumina slurry, ultrasonicated in ethanol and deionized water, and dried under nitrogen flow. The PtNPs / graphene oxide nanocomposite was ultrasonically dispersed in deionized water for 30 min, and then the dispersed suspension was dropped onto the surface of the glassy carbon electrode and dried at room temperature to obtain a PtNPs / graphene oxide modified glassy carbon electrode. S5. Preparation of nicotine molecularly imprinted polymer sensing electrode: The acetonitrile solution of pyridine, nicotine and potassium perchlorate is mixed to obtain an electropolymerization solution, and the electropolymerization solution is electropolymerized in the potential range of 0.1-1.6V by cyclic voltammetry, with a scanning rate of 50 mV / s and 10-15 cycles. After the electropolymerization reaction, the electrode is rinsed with acetonitrile, and then the electrode is immersed in a solution of NaCl and HCl, stirred for 30 minutes, and then rinsed with deionized water, and dried under a nitrogen flow, thereby obtaining a nicotine molecular imprinted polymer sensing electrode; S6. Preparation of tobacco product samples: Take tobacco samples, extract them with methanol or ethanol ultrasonically for 30 minutes, filter the extract and dilute it with phosphate buffered saline; S7. Nicotine detection in tobacco product samples: The nicotine molecular imprinted polymer sensing electrode was immersed in the tobacco extract diluted in step S6 for 10 minutes, after which the electrode was rinsed with phosphate buffered saline and transferred to fresh phosphate buffered saline for differential pulse voltammetry measurement. The nicotine concentration in the tobacco sample was determined using a calibration curve of a standard nicotine solution.
2. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S1, the mass ratio of graphite powder, concentrated sulfuric acid, potassium permanganate and sodium nitrate is 1:80-110:2-5:10-20; the volume ratio of the mixture and deionized water is 1:1.5-3; after heating, the volume ratio of the mixture, deionized water and hydrogen peroxide is 1:1-2:0.05-0.
2.
3. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S2, the volume ratio of the hexahydrate chloroplatinic acid solution to the sodium dodecyl sulfate solution is 1:1-2; and the mass ratio of the mixed solution to ascorbic acid is 200-300:
1.
4. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S3, the mass ratio of graphene oxide to deionized water is 1:2-4; the volume ratio of graphene oxide dispersion to PtNPs suspension is 1:0.1-0.
3.
5. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S4, the glassy carbon electrode is polished with 0.3 μm and 0.05 μm alumina slurries, respectively, and the mass ratio of the PtNPs / graphene oxide nanocomposite material to deionized water is 1:800-1200.
6. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S5, 0.1 M pyridine, 10 mM nicotine and 0.1 M potassium perchlorate in acetonitrile are mixed, and the volume ratio of pyridine, nicotine and potassium perchlorate in acetonitrile is 1:1-3:2-5 to obtain an electropolymerization solution.
7. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 6, characterized in that: In step S5, the electrode is immersed in a solution of 0.5 M NaCl and 0.1 M HCl, and the volume ratio of NaCl to HCl is 1:1-2.
8. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S6, the mass ratio of tobacco sample to extractant is 1:5-10, the extract is filtered through a 0.22 μm nylon syringe, and then diluted with a 0.1 M phosphate buffered saline solution with a pH of 7.4, and the volume ratio of the extract to the phosphate buffered saline solution is 1:5-10.
9. The method for detecting nicotine based on a molecular imprinting polymer sensor according to claim 1, characterized in that: In step S7, differential pulse voltammetry measurement is performed in the potential range of 0.2-0.8 V, with a pulse amplitude of 50 mV, a pulse width of 50 ms, and a step potential of 5 mV.
10. An application, characterized in that: Use of the method for detecting nicotine based on a molecular imprinting polymer sensor according to any one of claims 1 to 9 in detecting nicotine.